Viabilidade térmica de um forno solar fabricado com sucatas de pneus - Varela, Pedro Henrique de Almeida (2013)
The proposed design provides a solar furnace alternative, box-like, low-cost operation to be used in cooking, comprising three scrap tires to make the recycling thereof. The tires were coupled to each other, forming an enclosure, which stood on its bottom covered by a parable multiple mirrors made from a urupema (sieve indigenous) and the inner sides of the oven aluminum sheet painted black, obtained from beer cans, thus being made to obtain the increase in the concentration of solar radiation incident on the inside of the prototype studied. Two tires were attached, leaving an air layer between them, with the function of thermal insulation. The third tire aimed to support the other two and thermally insulate the bottom of the oven. Externally was placed a metal frame with flat mirrors to reflect the incident rays into the oven, having a mobility to correct the apparent motion of the sun. Its primary feature is the viability of clean, renewable energy to society by tackling the ecological damage caused by the large-scale use of wood for cooking food. The tests show that the furnace reached the maximum temperature of 123.8 °C and baking various foods such as pizza, bun, and other lasagne in an average time 50 minutes. Proves the feasibility of using the oven. Presenting still able to improve their performance with the addition of new materials, equipment and techniques